Propellants Reactivity Enhancement with Nanothermites. Issue 6 (26th September 2016) - Berthe, Jean‐Edouard; Comet, Marc; Schnell, Fabien; Suma, Yves; Spitzer, Denis
Abstract: Propellant grains (Vectan A1) were coated with a thin and stable layer (50 μm, 10 wt‐%) of a "green" sulfate‐based nanothermite (Na2 SO4 /Al). This flash composition was used herein as an internal pyrotechnic lighter to accelerate the ignition and the combustion of the propellant. The combustion of the modified propellant, which was tested in one‐end open tubes, propagates four orders of magnitude faster than the one of pristine Vectan A1. This tremendous effect was tuned by varying the proportion of coated Vectan A1 grains from 20 to 100 % in the samples. The percolation threshold is in between 20 and 40 %. Beyond this point, the effect can be improved by increasing the proportion of nanothermite‐coated propellant grains in the charge. Abstract :